The Effect of Elastic Band Application in Training Program of Basketball Players - Živković, Uroš; Hadži Pavlović, Đorđe (Sport - nauka i praksa, 2025)
The aim of this review paper is to analyze studies that have examined the impact of using elastic bands in basketball players’ training processes, as well as to provide a practical training program proposal incorporating elastic bands. The sample consisted of studies from electronic scientific databases, with a total of eight studies meeting the required inclusion criteria. The results, presented in tabular form, include descriptive statistics (anthropometric characteristics, sex and age), the duration and details of each training program implemented, and tests used to assess the effects of elastic band application in the selected studies. All analyzed studies confirmed a positive effect of elastic bands on at least one motor ability of basketball players, aligning with the hypothesized outcomes of the respective authors. Consequently, it can be concluded that elastic bands should be integrated into training programs all year round. Their use can be adjusted depending on the phase of the competitive season: from developing maximum force in conjunction with weights during the preseason, through individual application for enhancing maximal movement and running speed, to improving and maintaining specific abilities such as explosive power in jumps and rapid direction changes during the competitive period. Given their broad application, it is recommended that coaches incorporate elastic bands into training programs, ideally alongside weights or independently, in three weekly training sessions. Considering their extensive impact, their application should be tailored to the specific needs of individual athletes.